Design of Cloud Computing Based Gas Detection Systems using NodeMCU ESP8266 Microcontroller - Revy Cahya Alamsyah; Muhammad Benny Chaniago (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2019)
Liquefied Petroleum Gas (LPG) is a fuel that is currently widely used by the community in meeting their daily needs. Safety in the use of LPG) is one of the important aspects for Indonesian people both at home, eating-places, tourist attractions, campuses and other places that use LPG. Fires often occur caused by LPG leaks that are not realized by the owner and the people around him, causing fires. The fire caused by gas leakage not only harms the owner but also people who are not far from the fire. From these problems, the authors make a design of cloud computing-based detection system of gas leak using a microcontroller NodeMCU Esp8266 that can provide notifications via smartphone in case of fire and automatically do the first treatment by turning on the exhaust. Notifications sent via the smartphone appear not only when opening the application, but also when it does not open the application.